Investigation of collisions between electrons and excited atoms of potassium, rubidium and caesium - Pietruczuk, Aleksander; Stacewicz, Tadeusz; Wilska, Magdalena (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Results of measurements of the rate constants for electron impact induced transitions between selected levels of potassium (4P–6P), rubidium (5P–7P) and caesium (6P–8P and 6P–9P) are presented. The experiment was done in helium plasma produced by electric discharge. The plasma was doped with the atoms of interest at a concentration of about 1011 cm–3. The alkali atoms were excited to resonance level by a laser pulse. The rate constants for the investigated transitions were determined by the analysis of atomic fluorescence. The electron temperature was measured using a double probe method.
Optica Applicata, Vol. 36, 2006, nr 4, s. 489-497
Keywords: optyka; electron–atom collisions; excited atoms; plasma